1996
DOI: 10.1128/aem.62.2.522-528.1996
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and structure of hyphomicrobium populations in a sewage treatment plant and its adjacent receiving lake

Abstract: Budding methylotrophic bacteria resembling Hyphomicrobium spp. were counted for 12 months in a German sewage treatment plant by most-probable-number (MPN) methods. Influent samples contained up to 2 ؋ 10 4 cells ml ؊1 , activated sludge consistently contained 1 ؋ 10 5 to 5 ؋ 10 5 cells ml ؊1 , and the effluent contained 1 ؋ 10 3 to 4 ؋ 10 3 cells ml ؊1 . The receiving lake had only 2 to 12 cells ml ؊1 . Six morphological groups with different growth requirements could be observed among 1,199 pure cultures that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Hybridizations of samples taken from almost 1 year of operation indicated that the Hyphomicrobium cluster II organisms dominated over the Hyphomicrobium cluster I organisms by 3-to 12-fold. Holm et al (17) suggest that morphologically and nutritionally similar isolates of Hyphomicrobium may show a high level of genetic diversity and that Hyphomicrobium populations may vary seasonally. In this wastewater treatment plant the Hyphomicrobium populations showed genetic diversity but did not vary seasonally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridizations of samples taken from almost 1 year of operation indicated that the Hyphomicrobium cluster II organisms dominated over the Hyphomicrobium cluster I organisms by 3-to 12-fold. Holm et al (17) suggest that morphologically and nutritionally similar isolates of Hyphomicrobium may show a high level of genetic diversity and that Hyphomicrobium populations may vary seasonally. In this wastewater treatment plant the Hyphomicrobium populations showed genetic diversity but did not vary seasonally.…”
Section: Discussionmentioning
confidence: 99%
“…Hyphomicrobium spp. have been reported in both sewage treatment plants and adjacent waters (15,17,20). Recently, the 16S ribosomal DNA (rDNA) sequences for seven species of the genus Hyphomicrobium were published (30).…”
mentioning
confidence: 99%
“…The second dominant genus (22.1%) was aerobic, methylotrophic budding bacteria Hyphomicrobium ( Figure 2) (mostly H. zavarzinii and H. hollandicum; Table S2), characteristic in producing hyphal filaments during growth. Hyphomicrobium has been widely detected as a dominant member in Mn-deposits from worldwide locations, including freshwater pipelines [19] and sewage treatment plants [17]. Despite its abundance in Mn-deposits, the difficulty in its isolation and steady maintenance makes it still unclear whether or not Hyphomicrobium is indeed directly responsible for Mn(II) oxidation [19,31].…”
Section: Microbial Community Structure Analysismentioning
confidence: 99%
“…Water 2019, 11, x FOR PEER REVIEW 7 of 15 member in Mn-deposits from worldwide locations, including freshwater pipelines [19] and sewage treatment plants [17]. Despite its abundance in Mn-deposits, the difficulty in its isolation and steady maintenance makes it still unclear whether or not Hyphomicrobium is indeed directly responsible for Mn(II) oxidation [19,31].…”
Section: Microbial Community Structure Analysismentioning
confidence: 99%
“…The genus Hyphomicrobium (18) with presently eight species (7,22) and additional 29 DNA-DNA hybridization groups (10,11) belongs to the alpha group of the Proteobacteria (21). Hyphomicrobium facilis, H. facilis subsp.…”
mentioning
confidence: 99%